INTERACTION EFFECT OF VARIETIES AND PLANT SPACING, UNDER ULTRA HIGH DENSITY SYSTEM, ON GROWTH AND YIELD OF CASHEW (Anacardium occidentale L.) (Applied Biological Research, 2025)
An experiment was conducted at AICRP on Cashew in Bhubaneswar, Odisha, India, during the cropping seasons of 2022–23 and 2023–24 to assess the interaction between cashew varieties and planting densities under an ultra-high-density planting (UHDP) system. Three varieties viz., ‘VRI-3’, ‘NRCC Selection-2’, and ‘Balabhadra’ were tested at spacing of 2.5 m × 2.5 m, 3.0 m × 3.0 m, and 7.5 m × 7.5 m. The results revealed significant differences in yield and yield-related traits among cashew varieties under different plant densities. Adoption of UHDP significantly decreased trunk cross section area (36.07 cm²), average canopy spread (2.19 m), crown height (1.56 m), canopy volume (5.08 m³), total number of laterals m⁻² (22.29), number of flowering laterals m⁻² (12.60), and kernel weight (2.21 g) compared to the wider spacing of 178 plants ha⁻¹. The cultivar ‘NRCC Selection-2’ at 2.5 m × 2.5 m spacing achieved the highest nut yield (0.94 t ha⁻¹), whereas ‘VRI-3’ at 7.5 m × 7.5 m gave the lowest (0.18 t ha⁻¹). The cultivar ‘NRCC Selection-2’ exhibited superior performance across all the planting densities, attributed to its genetic potential and enhanced responsiveness to pruning.
Keywords: Cashew; NRCC Selection-2; ultra high density; varieties; yield